Cap-Assisted Technique versus Conventional Methods for Esophageal Food Bolus Extraction: A Comparative Study - Mahmoud Wahba; Ghada Habib; Ahmed El Mazny; May Fawzi; Mohamed A. Elfeki; Seham Sabry; Mahommad ELbaz; Sayed M Seif El Nasr (Korean Society of Gastrointestinal Endoscopy, 2019)
Background/Aims Food bolus impaction is the most common form of esophageal foreign body impaction observed in adults. Clinical guidelines recommend using the push technique or retrieval methods in such cases. The push technique can cause injuries in certain clinical situations. Notably, conventional retrieval methods are time and effort consuming. Cap-assisted endoscopic extraction of an impacted food bolus is an easy and effective technique; however, more data are needed for its validation. This study compared the capassisted extraction technique with conventional methods. Methods This prospective observational multicenter study compared the success and en bloc removal rates, total procedure time, and adverse events in both techniques.. Results The study included 303 patients who underwent food bolus extraction. The push technique was used in 87 patients (28.7%) and a retrieval procedure in 216 patients (71.3%). Cap-assisted extraction was performed in 106 patients and retrieval using conventional methods in 110 patients. The cap-assisted technique was associated with a higher rate of en bloc removal (80.2% vs. 15%, p<0.01), shorter procedure time (6.9±3.5 min vs. 15.7±4.1 min, p<0.001), and fewer adverse events (0/106 vs. 9/110, p<0.001). Conclusions Cap-assisted extraction showed no adverse events, higher efficacy, and a shorter procedure time compared with conventional retrieval procedures.